2012
DOI: 10.2478/s13382-012-0060-4
|View full text |Cite
|
Sign up to set email alerts
|

Anosmia after exposure to a pyrethrin-based insecticide: A case report

Abstract: We present the case of a subject developing anosmia, preceded by nasal transient irritation and short lasting phantosmia and torqosmia, upon re-entrance into a room treated with a pyrethrin-based insecticide. The concentration of the insecticide in the room is unknown, but relatively high levels are predicted basing upon the modality of exposure and by the irritation symptoms in the subject. Despite corticosteroids therapy, anosmia has persisted unmodified for more than three years; according to, and based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Despite the biological plausibility of a connection between pesticide exposure and OI in humans, empirical data are sparse and indirect. In addition to the aforementioned case report of anosmia following acute exposure to pyrethroids (Gobba and Abbacchini 2012), several cross-sectional studies (Ahman et al. 2001; Gudziol et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the biological plausibility of a connection between pesticide exposure and OI in humans, empirical data are sparse and indirect. In addition to the aforementioned case report of anosmia following acute exposure to pyrethroids (Gobba and Abbacchini 2012), several cross-sectional studies (Ahman et al. 2001; Gudziol et al.…”
Section: Discussionmentioning
confidence: 99%
“…We only know of one case report that documented olfactory dysfunction following high exposure to pesticide. Minutes after entering a poorly ventilated examination room treated by a pyrethrin-based insecticide for pest infestation, an Italian doctor developed nasal irritation and progressive loss of odor perception (Gobba and Abbacchini 2012). After days in the room, the doctor developed anosmia or a total loss of the sense of smell; the authors reported that anosmia persisted through the last clinical visit 3 y later and was therefore deemed permanent.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric lavage and emetics can also be employed. As there is no specific antidote early diagnosis with supportive management is required [ 13 ]. Optimization of airway, breathing and circulation is crucial as with any acute poisoning preferably in a center that provides a higher level of circulatory and ventilatory support.…”
Section: Discussionmentioning
confidence: 99%
“…One case study in humans details anosmia following exposure to a pyrethrin-based pesticide. 26 Recent research on honeybees and fish has implicated sublethal doses of pesticides in olfactory impairment. 27,28 Much larger groups of studies have implicated pesticides in neurodegenerative diseases 5,2932 and identified loss of olfactory function as an early and common symptom of these diseases.…”
Section: Discussionmentioning
confidence: 99%